2012
DOI: 10.1186/1754-9493-6-12
|View full text |Cite
|
Sign up to set email alerts
|

Does hyperthermic intraoperative chemotherapy lead to improved outcomes in patients with ovarian cancer? A single center cohort study in 111 consecutive patients

Abstract: BackgroundFor recurrent disease or primary therapy of advanced ovarian cancer, cytoreductive surgery (CRS) followed by adjuvant chemotherapy is a therapeutic option. The aim of this study was to evaluate the outcome for patients with epithelial ovarian cancer treated with hyperthermic intraoperative chemotherapy (HIPEC) and completeness of cytoreduction (CC).MethodsData were retrospectively collected from 111 patients with recurrent or primary ovarian cancer operated with the contribution of visceral surgical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 31 publications
2
18
0
1
Order By: Relevance
“…They found that CRS alone had a similar rate of major morbidity compared to HIPEC+CRS (26.7% vs 28.6%, respectively), however, CRS alone had a substantially higher 30-day post-operative mortality rate (11.1% vs 0%, respectively) [28]. The causes of death in this study were cardiac or pulmonary insufficiency in four patients, sepsis in three patients, multi-organ failure in two patients, and pulmonary embolism in one patient.…”
Section: Mortality and Morbiditymentioning
confidence: 82%
See 4 more Smart Citations
“…They found that CRS alone had a similar rate of major morbidity compared to HIPEC+CRS (26.7% vs 28.6%, respectively), however, CRS alone had a substantially higher 30-day post-operative mortality rate (11.1% vs 0%, respectively) [28]. The causes of death in this study were cardiac or pulmonary insufficiency in four patients, sepsis in three patients, multi-organ failure in two patients, and pulmonary embolism in one patient.…”
Section: Mortality and Morbiditymentioning
confidence: 82%
“…Selection bias likely accounts for these results, whereby patients with primary advanced ovarian cancers who improved following chemotherapy with taxol or carboplatin were given HIPEC, whilst those that did not respond did not receive HIPEC. days [24], 14±4 vs 10±4 days [30], 32.9 vs 27.5 days [28]). The likelihood of being admitted into ICU was also higher with the addition of HIPEC (100 vs 72.2% [28]).…”
Section: Mortality and Morbiditymentioning
confidence: 91%
See 3 more Smart Citations